IgG4-related intracranial disease. Issue 1 (February 2019) - Goulam-Houssein, Shahine; Grenville, Jeffrey L; Mastrocostas, Katerina; Munoz, David G; Lin, Amy; Bharatha, Aditya; Vlachou, Paraskevi A
IgG4-related disease (IgG4-RD) is a multi-organ chronic inflammatory process caused by infiltration of IgG4-positive plasma cells in one or more organs. Intracranial involvement has only recently become better recognized. Our case series adds to the growing literature on the varying presentations of intracranial IgG4 by describing the clinical and imaging findings of three patients who presented to our institution with intracranial involvement. Our first patient presented with a mass-forming IgG4 pachymeningitis mimicking a sphenoid wing meningioma, which is to our knowledge the largest mass-forming pachymeningitis published in the literature. Our second case depicts another presentation of extensive IgG4 pachymeningitis involving both cavernous sinuses and surrounding Meckel's caves. The third case describes a patient with presumed lymphocytic hypophysitis, which was later determined to be IgG4-related hypophysitis with concomitant pachymeningitis and perineural spread along the optic nerves. The delayed diagnoses in our cases illustrates the diagnostic challenge that clinicians face in differentiating intracranial IgG4-RD from other infiltrative diseases such as sarcoidosis, granulomatous disease, tuberculosis and lymphoma. Earlier consideration of IgG4-related hypophysitis and hypertrophic pachymeningitis in the differential diagnosis can prevent significant morbidity including unnecessary surgical intervention and organ failure secondary to extensive fibrosis.